2011
DOI: 10.1097/mao.0b013e31820e7614
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Magnetic Resonance Imaging Performed After Intratympanic Administration of Gadolinium in the Identification of Endolymphatic Hydrops in Patients With Ménière's Disease

Abstract: Perilymphatic enhancement defect of variable degrees is observed in the pathologic ear of every patient with MD. The consistency of this phenomenon in MD ears and the complete enhancement in most of the ears without MD safely enable to attribute these findings to endolymphatic hydrops. It is likely in the near future that imaging may be used to achieve a certain diagnosis of MD in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…The intravenous route of contrast administration is also less invasive and renders perilymph enhancement independent of the status of the round window membrane. 26,27 In a comparative study in patients with MD, however, 28 intratympanic contrast injection provided higher perilymphatic signal compared with intravenous administration. An additional advantage of the intravenous method is simultaneous examination of both labyrinths because provided the disease manifestation is unilateral, the nondiseased ear serves for comparison.…”
Section: Mr Imaging Visualization Of Ehmentioning
confidence: 99%
“…The intravenous route of contrast administration is also less invasive and renders perilymph enhancement independent of the status of the round window membrane. 26,27 In a comparative study in patients with MD, however, 28 intratympanic contrast injection provided higher perilymphatic signal compared with intravenous administration. An additional advantage of the intravenous method is simultaneous examination of both labyrinths because provided the disease manifestation is unilateral, the nondiseased ear serves for comparison.…”
Section: Mr Imaging Visualization Of Ehmentioning
confidence: 99%
“…29 Poor-to-absent contrast penetration into the perilymph has been reported after IT injection in up to 18% of patients, 9,30 suggesting a means to screen for potential poor responders to IT interventions. Nevertheless, series have not found a reliable correlation between the extent of en- dolymphatic distention and patient response to subsequent IT steroids, 16,18 and there has been variable correlation between imaging with summating potential/action potential ratios electrocochleography and vestibular-evoked myogenic potential. 17,25,31 These outcomes may be partially due to lack of standardization of criteria for severity based on imaging findings 8,12,13 but also may reflect the spectrum of findings through the range associated with the natural history of Menière disease.…”
Section: Discussionmentioning
confidence: 99%
“…7,[17][18][19] While the availability of 32-channel head coils has improved resolution to 0.4 ϫ 0.4 ϫ 0.8 mm, these volumetric sequences come at the cost of time, requiring up to 15 minutes for an acquisition, with potential for motion degradation and decreased SNR due to parallel imaging techniques. 20,21 A recent publication has shown reduced acquisition time to 5 minutes 26 seconds but at the cost of resolution, achieving only 0.7 ϫ 0.7 ϫ 0.8 mm.…”
mentioning
confidence: 99%
“…To overcome this problem, many studies have attempted to visualize endolymphatic hydrops using magnetic resonance imaging (MRI) and intratympanic (IT) injection of gadolinium (Gd) Nakashima et al, 2007;Shimono et al, 2013;Suzuki et al, 2011;Yamazaki et al, 2012;Zou et al, 2009]. With the advancement of MRI imaging of the inner ear microstructures, we are now able to detect endolymphatic space distention in living patients with Mé-nière's disease [Fiorino et al, 2011;Fukuoka et al, 2012;Nakashima et al, 2007].…”
Section: Introductionmentioning
confidence: 97%
“…Some authors have preferred intravenous injection over IT application Sano et al, 2012]. As for the optimal timing of MRI after Gd application, previous studies have shown that inner ear enhancement is most pronounced 24 h after transtympanic administration of Gd agents [Fiorino et al, 2011;Fukuoka et al, 2012;Nakashima et al, 2007], 4 h after intravenous administration in human subjects [Carfrae et al, 2008;Naganawa et al, 2006].…”
Section: Introductionmentioning
confidence: 99%